Clinical studies on enteric fever - Arjyal, A; AMIT ARJYAL (2014)
I performed two randomised controlled trials (RCTs) to determine the best treatments for enteric fever in Kathmandu, Nepal, an area with a high proportion of nalidixic acid resistant S. Typhi and S. Paratyphi A isolates. I recruited 844 patients with suspected enteric fever to compare chloramphenicol versus gatifloxacin. 352 patients were culture confirmed. 14/175 patients treated with chloramphenicol and 12/177 patients treated with gatifloxacin experienced treatment failure (HR=0.86 (95% CI 0.40 to 1.86), p=0.70). The median times to fever clearance were 3.95 and 3.90 days, respectively (HR=1.06 [CI 0.86 to 1.32], p=0.59). The second RCT compared ofloxacin versus gatifloxacin and recruited 627 patients. Of the 170 patients infected with nalidixic acid resistant strains, the number of patients with treatment failure was 6/83 in the ofloxacin group and 5/87 in the gatifloxacin group (Hazard Ratio, HR=0.81, 95% CI 0.25 to 2.65; p=0.73); the median times to fever clearance were 4.7 and 3.3 days respectively (HR=1.59 [CI 1.16 to 2.18], p=0.004). I compared conventional blood culture against an electricity free culture approach. 66 of 304 patients with suspected enteric fever were positive for S. Typhi or S. Paratyphi A, 55 (85%) isolates were identified by the conventional blood culture and 60 (92%) isolates were identified by the experimental method. The percentages of positive and negative agreement for diagnosis of enteric fever were 90.9% and 96.0%, respectively. This electricity free blood culture system may have utility in resource-limited settings or potentially in disaster relief and refugee camps. I performed a literature review of RCTs of enteric fever which showed that trial design varied greatly. I was interested in the perspective of patients and what they regarded as cure. 1,481 patients were interviewed at the start of treatment, 860 (58%) reported that the resolution of fever would mean cure to them. At the completion of treatment, 877/1,448 (60.6%) reported that they felt cured when fever was completely gone. We suggest that fever clearance time is the best surrogate for clinical cure in patients with enteric fever and should be used as the primary outcome in future RCTs for the treatment of enteric fever.